(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2024)
The article examines the influence of the modern globalized economic environment on the activities of enterprises operating in the field of foreign economic activity and facing a large number of risks in the course of their operation, in particular due to the influence of force majeure circumstances. The importance of risk management for ensuring the financial stability of enterprises in the conditions of increasing risks and threats to economic activity is determined. The impact of risk management on the financial stability of enterprises in foreign economic activity, especially in cases of force majeure, is studied. It has been proven that risk management in the context of foreign trade involves the identification, assessment, management and monitoring of risks that may arise. It has been determined that effective risk management allows business entities to properly adapt to changes in the economic environment and reduces the likelihood of financial losses in the event of force majeure events, such as the cessation of trade, sudden changes in exchange rates, or military or political crises. Strategies for including risk management in the management processes of enterprises based on analytical assessments and practical experience of ensuring financial stability are considered. Methods of risk identification, development of risk minimization strategies and mechanisms of risk control during foreign economic operations were studied. The objective necessity of forming an effective risk management system in the management mechanism of economic entities to ensure the financial stability of enterprises in foreign economic activity, especially in connection with force majeure circumstances, has been proven. The issue of implementing risk management at the level of strategic and operational management of enterprises is considered. Methods of risk forecasting, analysis of their impact on financial indicators and development of effective action plans to reduce possible negative consequences of exposure to risks and threats were analyzed. The necessity of introducing international risk management standards into the activities of Ukrainian enterprises, which contribute to increasing their level of competitiveness and compliance with international requirements, has been proven. The need for constant improvement of the risk management system and the introduction of corrections in enterprise management strategies, taking into account changes in the external environment, was identified. It is proposed to introduce approaches to the management of enterprises focused on effective management of financial risks in force majeure situations in order to ensure their financial sustainability and stability.